(untitled) (Revista Rupturas, 2022)
This paper focus on the religious and political issue in Brazil from a socio-historical perspective. In recent years, we have seen the rise of the right-wing, anarcho-capitalist biopower in socio-political and reactionary-conservative terms in religious terms. How was the emergence of the current religious-political panorama possible? There are two complementary interpretative hypotheses: the construction of a conservative and reactionary religious-political camp and neoliberal social and economic changes. The research methodology is qualitative and primary and secondary documentary sources on contemporary Brazilian religion and politics were used.